Primary Care Providers' Perspectives on Prescribing Antidepressant Medication to Latino Immigrant Patients: A Preliminary Study. Issue 3 (March 2020) - Kirkpatrick, Laura; Watson, Maria Rosa; Serrano, Adriana; Campoli, Marcela; Kaltman, Stacey I.; Talisman, Nicholas; Green, Bonnie L.
Abstract : Abstract: Latinos in the United States are less likely to take antidepressants than non-Latino whites, and more likely to prefer depression treatment in primary care. This preliminary study comprised focus groups (2) with primary care providers (12) serving uninsured immigrant Latinos regarding their experiences prescribing and counseling patients about antidepressants. Barriers and challenges included health literacy, language barriers, and illiteracy; perceived stigma; patients' concerns about addiction, polypharmacy, and adverse effects; time constraints of office visits; and difficulty discussing comorbid posttraumatic stress disorder. Messages providers try to share with patients included allowing time for medications to work, taking medications daily as prescribed, mechanisms of action, weighing risks versus benefits, and flexible options for treatment. Providers' recommendations for improving this process included better low-literacy, culturally appropriate written materials with pictures or videos discussing depression. More research is needed to understand patients' and providers' needs in optimizing counseling about antidepressants, particularly regarding underserved and at-risk US populations.